Finite element analysis of stress distribution on residual root structure in socket shield procedure following immediate dental implant placement: an in vitro study - Aniket Shinde; V.N.V Madhav; Ravinder S Saini; Vishwanath Gurumurthy; Rayan Ibrahim H Binduhayyim; Seyed Ali Mosaddad; Artak Heboyan (BMC, 2024)
Abstract Background The success of implants in the socket shield technique relies on stress experienced by root fragments within the socket. Although there is no consensus on optimal root fragment thickness, varying thicknesses and dynamic implant placement induce stress in various directions and degrees. This study aimed to assess biomechanical response and stress distribution across different root fragment thicknesses in the socket shield procedure. Methods This in vitro study was conducted to assess and compare the stress distribution on residual root structures of varying thicknesses positioned within the labial aspect of the maxillary incisor socket during immediate implant placement of standard dimensions. The procedure involved applying an insertional torque of 40 Ncm, and the analysis was conducted using finite element analysis software. Results Utilizing the Numerical Technique with Abaqus software for explicit dynamics, von Mises stress and principal strain were analyzed on the root structure and bone under nonlinear contact conditions during implant torque application. For Model A, a loading torque of 40 Ncm was applied vertically on the implant, along with a horizontal force of 20 N on the root structure and bone. Results indicated maximum stress of 12.68 MPa on the root structure with a thickness of 0.5 mm and 5.61 MPa on the bone, with principal strains of 6.82E-03 and 4.10E-03, respectively. In Model B, with a root structure thickness of 1.0 mm, the maximum stress increased to 19.70 MPa, while the bone stress rose to 9.51 MPa, with principal strains of 1.03E-02 and 6.09E-03. Model C, with a root structure thickness of 1.5 mm, exhibited a maximum stress of 21.58 MPa on the root and 10.12 MPa on the bone, with principal strains of 1.16E-02 and 6.10E-03. Lastly, in Model D, with a root structure thickness of 2.0 mm, the maximum stress on the root structure and bone escalated to 28.74 MPa and 11.38 MPa, respectively, with principal strains of 1.55E-02 and 8.31E-03. Conclusions As the thickness of the shield increases (ranging from 0.5 to 2 mm) in socket shield procedures with immediate implant placement, both stress on the root fragment and bone and principal micro-strain escalate. However, employing a shield thickness within the range of 0.5 to 2 mm does not lead to any adverse stress generation on the residual root fragment. However, for enhanced safety, it is recommended to restrict the maximum diameter and extension of the root fragment to 1.5 mm when considering implant sizes and socket diameter for the socket shield technique.